MENELAAH EKSISTENSI MANUSKRIP KHUTBAH GULUNGAN ABAD XVIII PERSPEKTIF KONTEKSTUAL - Ighfirli Saputra (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Khotbah manuscripts are an important piece of evidence to understand the dynamics of worship in the past. The texts of the khotbah are in Arabic and rolled up. With the khotbah manuscript as the object of study, this research seeks to search: why is the khotbah manuscript in the form of a scroll? Why is the text in Arabic and developing which in fact the population of the nusantara socio-culturally is non-Arabic? viewed from the perspective of contextual Islam in a socio-historical context in Fazlur Rahman's Double Movement method. It is concluded that the presence and existence of this khutbah manuscript illustrates the entry of Islam in Indonesia not being rigid and textual, but rather a process that takes into account and adapts existing contextual phenomena. The use of Arabic in the khutbah is inseparable from the factor of Islamization in Indonesia and it is assumed that they have just touched Islam and there are no scholars in each region who are proficient in Arabic. The use of the Daluwang text in the form of a scroll is one form of ijtihad and acculturation efforts to make it easier for other community groups to be able to carry out khutbah activities.